Ionizable polymeric micelles (IPMs) for efficient siRNA delivery - Ziyu Zhou; Yu Feng; Mingzhou Jiang; Zijun Yao; Jing Wang; Feng Pan; Rulan Feng; Chong Zhao; Yinyu Ma; Jinge Zhou; Lei Sun; Xiaotian Sun; et al. (Nature Communications)
Abstract Lipid nanoparticles (LNPs) are widely used for nucleic acid delivery but face challenges like limited targeting and accelerated blood clearance (ABC) effect. We design three ionizable oligomers (IOs) that, with polylactide-polyethylene glycol (PLA-PEG), form a potential siRNA delivery system, named Ionizable Polymeric Micelles (IPMs). The siRNA encapsulated IPMs escape from lysosomes upon cellular uptake, and silence the target gene. A fibroblast activation protein inhibitor modified IPMs (FAPi-IPMs) show higher targeting for activated hepatic stellate cells (HSCs) compared to that for hepatocytes, silencing both HSP47 and HMGB1, reducing collagen secretion and liver inflammation, thereby treating fibrosis. Moreover, IPMs and FAPi-IPMs mitigate ABC effect and produce fewer PEG antibodies than LNPs, and show minimal apolipoprotein adsorption in vivo compared with LNPs, differentiating their targeting effects from LNPs. In conclusion, IPMs represent a nucleic acid delivery system with alternative targeting ability and reduced ABC effect.